Effect of Curcumin Plus Piperine on Redox Imbalance, Fecal Calprotectin and Cytokine Levels in Inflammatory Bowel Disease Patients: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Amylly Sanuelly da Paz Martins; Orlando Roberto Pimentel de Araújo; Amanda da Silva Gomes; Fernanda Lívia Cavalcante Araujo; José Oliveira Junior; Joice Kelly Gomes de Vasconcelos; José Israel Rodrigues Junior; Islany Thaissa Cerqueira; Manoel Álvaro de Freitas Lins Neto; Nassib Bezerra Bueno; Marília Oliveira Fonseca Goulart; Fabiana Andréa Moura (MDPI AG, 2024)
The development and course of inflammatory bowel disease (IBD) are significantly influenced by inflammation and oxidative stress. Antioxidant therapy is a promising therapeutic option to enhance the clinical results of these individuals in this particular scenario. The purpose of this study is to assess the impact of curcumin, with or without piperine, on cytokines, fecal calprotectin (CalF), and oxidative stress enzymatic and non-enzymatic indicators in patients with IBD. Methods: Patients with Crohn's disease (CD) or ulcerative colitis (UC) who were at least 18 years old and had intact liver and kidney function participated in this randomized, double-blind trial (trial registration: ensaiosclinicos.gov.br as RBR-89q4ydz). For 12 weeks, participants were randomly assigned to one of three groups: placebo, curcumin (1000 mg/day), or curcumin plus piperine (1000 mg + 10 mg/day). In order to examine oxidative stress indicators, CalF, and pro-inflammatory cytokines, blood and fecal samples were obtained, both prior to and following the intervention time. Results: After adjusting for age, sex, and type of IBD, the curcumin plus piperine group had substantially higher serum levels of superoxide dismutase (SOD) than the placebo group (4346.9 ± 879.0 vs. 3614.5 ± 731.5; p = 0.041). There were no discernible variations between the groups in CalF, inflammatory markers, or other indicators of oxidative stress. Conclusions: In patients with inflammatory bowel disease (IBD), our study indicates that a 12-week curcumin plus piperine treatment effectively increases enzymatic antioxidant defense, especially SOD. These results demonstrate the potential therapeutic benefits of managing redox imbalance in individuals with IBD.